Conductivity Dispersion Characteristic of Oilwell Cement Slurry during Early Hydration. - Syahrir, Ridha (publisher@ijens.org, 2010)
Than influence of water to cement ratio and degree of hydration is evaluated and express in the form and magnitude and frequency effect at above cutoff frequency.it is observed that,teh magnitude of conductivity dispersion increases with reduction in water content and pore volume. At initial hydration, the dispersion characteristic appears in minimum value and rises as hydration continue.